Makna Budaya dalam Makanan Arsik Ikan Mas: Kajian Semiotika Kuliner Lokal Masyarakat Batak Toba - Hadawiyah, Andina; Caroline, Emya Gita; Yani, Indri; Sitompul, Monalisa Senada (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research explores the symbolic meanings contained in the traditional dish of arsik fish using the semiotic perspective of Charles Sanders Peirce. In Batak Toba culture, arsik is not merely considered food, but as a medium for conveying social, spiritual, and cultural values. This study was conducted with a qualitative descriptive approach, through direct observation at customary ceremonies, interviews with local informants, visual documentation, and relevant literature studies. The analysis was carried out based on three categories of signs in Peirce's theory: icon, index, and symbol. Iconic characteristics were found in the presentation of arsik, which maintains its whole form, distinctive color, and large size, reflecting values of integrity and hope. Meanwhile, indexical aspects emerge from the connection of arsik with meanings of fertility, harmony, and blessings.Symbols are interpreted through the role of arsik as a marker of cultural identity and a spiritual means in various customary rituals such as weddings, seven-month ceremonies, and the lifting of sidi. This finding shows that traditional food like arsik is a medium of cultural communication rich in meaning and plays an important role in preserving local cultural heritage.